Influence of extended aging on beef quality characteristics and sensory perception of steaks from the gluteus medius and longissimus lumborum. (December 2015) - Colle, M.J.; Richard, R.P.; Killinger, K.M.; Bohlscheid, J.C.; Gray, A.R.; Loucks, W.I.; Day, R.N.; Cochran, A.S.; Nasados, J.A.; Doumit, M.E.
Abstract: The objective was to determine the influence of post-fabrication aging (2, 14, 21, 42, and 63 days) on beef quality characteristics and consumer sensory perception of gluteus medius (GM) and longissimus lumborum (LL) steaks. Lipid oxidation and aerobic plate counts increased ( P  < 0.05) with longer aging periods and retail display times. An aging period by day of retail display interaction ( P  < 0.05) was observed for a* and b* values for both muscles and L* values for the LL. Warner–Bratzler shear force values decreased ( P  < 0.05) with longer aging for the LL, while no difference was observed for the GM. Consumer panel results demonstrated that longer aging periods increased ( P  < 0.05) tenderness of both muscles. Our results indicate that extended aging reduces retail color stability yet has positive effects on consumer perception of tenderness of beef loin muscles. Highlights: USDA Select beef strip loin and top sirloin butts were aged for up to 63 days. Consumer perception of strip loin tenderness improves up to 14 days of aging. Perception of top sirloin tenderness is optimized between 21 and 42 days of aging. Extended aging reduces retail shelf-life of beef strip loin and top sirloin butts.